Catalytic activity in vitro of the human protein kinase ASK1 mutants: Experimental and molecular simulation study. (August 2022) - Xie, Yayu; Cao, Pei; Qin, Yuan; Wu, Xiru; Huang, Bingyao; Liu, Kai; Liu, Yonghong
Abstract: Kinases have become an important class of targets for drug discovery since the milestone approval of imatinib in 2001. Although a great success has been achieved for targeting kinases with over 70 inhibitors approved by the FDA, it is inevitable that drug resistance would emerge during treatment. Thus, assessment of the kinase mutations is an essential issue for the development of the next generation inhibitors. Apoptosis signal-regulating kinase 1 (ASK1) is a crucial regulator of classical mitogen-activated protein kinase cascade that is being explored under several clinical trials as a promising target. Herein, we investigate the catalytic activity in vitro of ASK1 by constructing two mutants: M754T and H729L, from gatekeeper and αC-helix, respectively. Compared to wild type, the mutation of M754T and H729L results in a roughly 3-fold and 2-fold decrease in binding affinity experimentally. In addition, their binding modes with substrate are theoretically predicted and compared by molecular dynamics. Trajectory analyses of simulations indicate that the decrease of binding affinity should be attributed to the loss of H-bond interaction with gatekeeper methionine. Unexpectedly, the conformation of αC-helix in H729L mutant did not alter significantly during the simulations, although the putatively important H-bond with H729 is lost. These simulations showed the regulatory role of H729 in αC-helix is maintained by leucine residue through the interaction with non-polar residues around H729 site. Graphical Abstract: ga1 Highlights: Catalytic activity of ASK1 and its mutations were evaluated by both in vitro experiment and molecular dynamics studies. Mutation of the gatekeeper (M754T) of ASK1 kinase decreased the binding affinity about 3-fold. M Mutation of H729L from αC-helix resulted about 2-fold loss of catalytic activity. The loss of H-bond with gatekeeper should be responsible for the experimental reduction of catalytic activity. The conformation of αC-helix was maintained under simulation for H729L mutant through non-polar interactions.